An Inpouring Review on the Current Liquidity Crisis in Zimbabwe - Banele Dlamini; Leonard Mbira (An Overview on Business, Management and Economics Research Vol. 3, 2023)
This study paper tries to investigate the reasons behind the liquidity problem that the Zimbabwean economy is now experiencing. In financial economics, a liquidity crisis is an acute shortage of liquidity. Liquidity may refer to market liquidity (the ease with which an asset can be converted into a liquid medium, e.g. cash), funding liquidity (the ease with which borrowers can obtain external funding), or accounting liquidity (the health of an institution’s balance sheet measured in terms of its cash-like assets). Since the advent of the multi-currency system in 2009, which had an impact on the economic development of Zimbabwe, the liquidity problem has plagued banks and businesses alike. The study used survey design and researcher-administered questionnaires were used to collect data from the respondents located in Harare, Bulawayo, Gweru and Masvingo. Out of the 200 questionnaires issued 150 were successfully completed resulting in a response rate of 75%. The study also used secondary data obtained from government agencies on export and import performance, focusing on the multi-currency regime (2009-2017). SPSS AMOS was used to test the hypothesis raised and generated a path modeling determining the size and strength of the direct and indirect influence between the predictor variables and the downstream variable. The analysis highlights the following antecedents as major causes that have an impact on the present liquidity crisis: public and investor trust, nation risk, externalization of money, illegal financial flows, and net export performance. The findings also indicated that the present liquidity crisis was not significantly impacted by the central bank’s lack of a lender of last resort position. In order to handle the liquidity problem, it is advised that the government concentrate on the aforementioned precursors.